Manajemen Pelayanan dan Infrastruktur Haji Pendekatan Gender untuk Efisiensi dan Kenyamanan Jamaah Haji Perempuan di Indonesia - Aedi, Ulul Aedi; Budiyono, Alief (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2026)
This article aims to describe and analyze the management of Hajj services in Indonesia using a gender approach. This research also aims to identify the existence and adequacy of gender-based Hajj infrastructure in Indonesia. The urgency of this goal is based on: 1. The commitment of the Ministry of Religious Affairs of the Republic of Indonesia to provide gender-based Hajj services. 2. Female Hajj pilgrims constitute the majority of pilgrims in the SISKOHAT data. 3. The issue of Fiqh for women remains an unresolved issue. The method used is descriptive qualitative with a case study approach. Data collection techniques were conducted through observations at the Central Java Ministry of Religious Affairs office and the Donohudan Hajj Dormitory. Data collection was also conducted through interviews with Haidar, the manager of the Donohudan Hajj Dormitory, and H. Fitiyanto, Head of the Hajj and Umrah Organization Division of the Central Java Ministry of Religious Affairs Regional Office. Interviews were also conducted with female Hajj pilgrims who were going on Hajj in 2025 and did not have a companion or mahram, Mrs. Rohmatun from Semarang Regency. The perspectives used are Total Quality Management (TQM) and Gender Analysis Pathway (GAP). The results show that the service and infrastructure management provided by Indonesian Hajj organizers exhibits a gender-neutral status rather than a gender-responsive one. This can be seen from the number of mentors that still does not meet needs, infrastructure that is not yet gender responsive, and regulations that are still general in nature. However, Hajj organizers have demonstrated a commitment to providing gender-responsive services and infrastructure. This commitment has been demonstrated by year-on-year improvements. This article can add to the theory of gender-based services in the organization of the Hajj pilgrimage. It also contributes to organizers' efforts to improve the quality of services and infrastructure.